Pelatihan Pengembangan Media Pembelajaran Berbasis Web Go Pai Bagi Guru Pai Di Jawa Tengah - Fihris; M. Rikza Chamami; Hery Nugroho; Ahmad Taufik (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2022)
This Lecturer Service Activity aims to facilitate training in the development of GO PAI web-based learning media for Islamic Religious Education Teachers in Central Java. This service is a form of collaboration to increase teacher competence between PAI UIN Walisongo Semarang and MGMP PAI SMA SMA Jawa Tengah. It is felt that the involvement of the Central Java SMA PAI MGMP in this training activity is felt to be more representative and on target. To achieve these goals this community service activity is carried out using the Community Based Research method. While the data collection techniques used were focus group discussions, in-depth individual interviews, questionnaires, observation, and documentation. In this activity the researchers attempted to uncover the problems and challenges of PAI teachers, especially high schools in Central Java in developing learning media in the digital era. Thus, the content of learning media development will be more in line with the needs in the field. In addition, the success rate of this training will also be evaluated. The research team measured the level of ability and understanding of participants or teachers in understanding and developing GO PAI Web-based learning media, as well as the ability to apply them to teaching and learning activities. The results of this service are in the form of GO PAI web-based learning media that can be utilized by PAI teachers in Central Java. This dedication is expected to be a form of concrete evidence of the contribution of the academic community of the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training (FITK) UIN Walisongo in the world of education.